The Influence of Culinary Destination Image and Tourism Motivation on the Intention to Visit South Korea - Talita, Eunike; Clara, Natasha; Harianto, Agung (Accounting Department, School of Business and Management - Universitas Kristen Petra, 2024)
This study aims to determine the effects of culinary destination image and tourist motivation on the intention to visit South Korea. It explores the role of attitude as a mediating variable and examines the direct effects of these factors on visitation intention. A total of 129 respondents were obtained using both online and offline questionnaires. The research method makes use of PLS-SEM analysis. The findings indicate that the image of culinary destinations and tourist motivation significantly influences attitude. Furthermore, attitude significantly impacts visiting intentions. Tourist motivation directly affects visiting intentions. Attitude serves as a mediating variable linking the image of culinary destinations and tourist motivation to visiting intentions. Additionally, the image of culinary destinations has an indirect effect on visiting intentions.